2015
DOI: 10.1002/anie.201502286
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Long‐Lived Intermediate States in the Complex Folding Pathway of the Human Telomeric G‐Quadruplex

Abstract: The energy landscapes of human telomeric G-quadruplexes are complex, and their folding pathways have remained largely unexplored. By using real-time NMR spectroscopy, we investigated the K(+)-induced folding of the human telomeric DNA sequence 5'-TTGGG(TTAGGG)3 A-3'. Three long-lived states were detected during folding: a major conformation (hybrid-1), a previously structurally uncharacterized minor conformation (hybrid-2), and a partially unfolded state. The minor hybrid-2 conformation is formed faster than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
128
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(143 citation statements)
references
References 39 publications
14
128
1
Order By: Relevance
“…We therefore expect that the major long-lived subpopulation (E≈0.73) is likely to represent the hybrid 1 conformation, whereas the short-lived subpopulation can be attributed to the hybrid 2 conformation. Recent time-resolved NMR experiments suggest similar structural assignments for the G4s formed from an analogous telomeric sequence (29). It should be noted that the parallel G4 conformation appears at similar transfer efficiencies (E≈0.71) as the hybrid conformations (Supplementary Figure S6).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…We therefore expect that the major long-lived subpopulation (E≈0.73) is likely to represent the hybrid 1 conformation, whereas the short-lived subpopulation can be attributed to the hybrid 2 conformation. Recent time-resolved NMR experiments suggest similar structural assignments for the G4s formed from an analogous telomeric sequence (29). It should be noted that the parallel G4 conformation appears at similar transfer efficiencies (E≈0.71) as the hybrid conformations (Supplementary Figure S6).…”
Section: Resultsmentioning
confidence: 87%
“…In our experiments with a G-triplex forming sequence such stable partially folded structures were not detected and are thus unlikely to contribute to any of the high E states here (Supplementary Figure S8). It should, however, be noted that we expect the unfolded state of G4s to be represented by a dynamic ensemble of a number of different unfolded and transiently formed partially folded conformations (29), possibly including G-hairpins and G-triplexes that may appear as a relatively broad peak at low transfer efficiencies in our single-molecule FRET histograms.…”
Section: Discussionmentioning
confidence: 97%
“…However, taking into account that molecular modeling shows significant cation affinity for the triplets (49), and that the control sequences used to subtract nonspecific adducts contained fewer than three G-tracts, a G-triplex structure is a good candidate for our low-abundance 1-K + intermediate 1a. Based on existing data (67), we attributed the firstly folded 2-K + hybrid G-quadruplex to the hybrid-2, whereas the hybrid-1 is formed at longer time scales. The rate constants then suggest that intermediate 1a is structurally closer to the hybrid-2 than to the hybrid-1 structure.…”
Section: Discussionmentioning
confidence: 92%
“…The branched reaction model 0×(1|2|2) with two different 2-K + complexes is derived from a recent paper from the Schwalbe group (67). The authors demonstrated by NMR that, for 24TTG and 26TTA, the hybrid-2 is formed first before unfolding to form the hybrid-1.…”
Section: Resultsmentioning
confidence: 99%
“…Competition between the hybrid-1 and hybrid-2 arrangements has been explicitly shown to determine the folding kinetics of the final stage of folding of 5′-TTGGG(TTAGGG) 3 A-3′ in the presence of K + using time-resolved NMR. 51 While the hybrid-1 arrangement has been determined to be the thermodynamic minimum, the kinetically more accessible hybrid-2 structure acted as the main competing fold, temporarily dominating the population. This experimental finding is consistent with theoretical models of GQ folding suggesting that Htel GQ folding is a multipathway process that can be best understood using the kinetic partitioning mechanism with diverse GQ folds acting as the dominant free energy basins on the free energy landscape.…”
Section: Introductionmentioning
confidence: 99%